PENERAPAN STANDARISASI UPAH MINIMUM BERDASARKAN SURAT KEPUTUSAN GUBERNUR RIAU NOMOR.1358/XI/2016 TENTANG UPAH MINIMUM KABUPATEN/KOTA SE PROVINSI RIAU TAHUN 2017 (Studi Kasus Badan Usaha Perbengkelan Kecamatan Sail) - Wahyu Hafzi; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Wages in practice must be in accordance with the provisions of applicablelegislation that is based on Law No. 13 of 2003 on Employment and also based onthe government's determination of provincial minimum wage and city minimumwage, namely Decree of Governor of Riau No. 11735 / XI / 2016. Application ofwages made by employers should not be lower than the applicable provisions. Iflower than the applicable provisions then null and void. In many cases there arestill many entrepreneurs who have not been able to pay wages based onPekanbaru City minimum wage in Sail District. The purpose of writing thesisnamely; First, the application of standardization of minimum wage of Pekanbarucity to workshop business sector sector in 2017; Secondly, obstacles faced byprivate entities in implementing minimum wage city Pekanbaru in 2017; Third,efforts made by employers and government in applying minimum wage policy ofPekanbaru year 2017.This type of research can be classified in sociological research. From theresearch results three points that can be concluded, Firstly, the application ofminimum wage standards is not applied based on the Decree of the Governor ofRiau Number: Kpts. 1058 / XI / 2016 Regarding Minimum Wage of Regency/Cityin Riau Province 2017 Second, Constraints faced by employers in applyingminimum wage for worker in Sail Sub-district are factors of Production Cost,employee education level, weak legal awareness of workers. Third, Efforts toovercome obstacles made by the Department of Manpower and employers is byway of deferring payment of minimum wage in accordance with applicableregulations, and conduct surveys and socialization of employers and workers inPekanbaru City. First, For employers, should pay more attention to the welfare oftheir workers, because workers are the most important asset owned by acompany; Second, For local government, to pay more attention to the wages givenby the company to its employees and play an active role in addressing theseminimum wage issues , Third, For employees, to be more active again to questionwages or salaries that are not in accordance with the provisions applicable in thiscase based on the Decree of the Governor of Riau.Keywoard: Wage – Application – Protection - Laborers